PROCESSING AND EVALUATION OF PUMPKIN CAKE (CUCURBITA MOSCHATA) - Campos, Érica Trindade; Cardoso, Bruno Trindade; Ramos, Semíramis Rabelo Ramalho; Carvalho, Michelle Garcêz; Santos, Daniel Oliveira (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
Pumpkin (Cucurbita moschata) is a vegetable traditionally consumed by the population in Brazil, especially in the Northeast region, that serves as an important source of vitamin A. Then, the pumpkin has been used for the elaboration of new food products. The aim was to formulate cakes containing freeze-dried pumpkin flour (pulp and peel), and to evaluate their sensory and chemical characteristics. Three cake formulations were prepared: F1 (without pumpkin flour), F2 (10% substitution of wheat flour with freeze-dried pumpkin flour) and F3 (20% substitution of wheat flour with freeze-dried pumpkin flour). Samples were evaluated microbiologically (coliforms at 35°C, coliforms at 45°C and salmonella spp.), sensorially based on ranking for preference (ordering test), in terms of acceptance (hedonic scale) and consumers’ purchase intentions by 80 untrained testers. Cakes’ chemical characteristics (moisture, ash, protein, lipids, carbohydrates and carotenoids) and color (by colorimetry) were evaluated. Formulations F2 and F3 had similar acceptance and purchase intentions. However, F3 was the most preferred formulation in terms of sensory attributes. The addition of freeze-dried pumpkin flour increased the percentage of ashes and carotenoids, as well as it intensified the color, making F2 and F3 more sensorially attractive. Pumpkin flour improved the sensory characteristics and nutritional value of the formulated cakes.